Pengaruh Ukuran Perusahaan, Return On Asset Dan Winner/Loser Stock Terhadap Praktik Perataan Laba (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Mulyanto, Mulyanto; Wibowo, Raden Arief (IAIN Surakarta, 2020)
This study aims to obtain empirical evidence about the influence of company size, return on assetsand winner / loser stock on income smoothing practices (empirical studies on manufacturing companies listed on the Indonesia Stock Exchange). The independent variables used in this study are company size, return on assets and winner / loser stock. The dependent variable used in this study is the practice of income smoothing. The object of this research are all manufacturing companies listed on the Indonesia Stock Exchange in 2014-2017. The number of companies sampled in this study were 177 companies over 4 periods, namely 2014-2017. The sampling method uses purposive sampling, while the method of data analysis uses logistic regression analysis. The results of this study indicate that firm size has no significant effect on income smoothing practices, return on assets does not significantly influence earnings smoothing practicesand winner / loser stock has no significant effect on income smoothing practices.Keywords: Total Assets, Return on Assets, Winner/Loser Stock, Eckel Index